Plant-Mediated Green Synthesis of Ag NPs and Their Possible Applications: A Critical Review - Darbin Kumar Poudel; Purushottam Niraula; Himal Aryal; Biplab Budhathoki; Sitaram Phuyal; Rishab Marahatha; Kiran Subedi (Journal of Nanotechnology)
The potential applications of Ag NPs are exciting and beneficial in a variety of fields; however, there is less awareness of the new risks posed by inappropriate disposal of Ag NPs. The Ag NPs have medicinal, plasmonic, and catalytic properties. The Ag NPs can be prepared via physical, chemical, or biological routes, and the selection of any specific route depends largely on the end-use. The downside of a physical and chemical approach is that it requires a wide space, high temperature, high temperature for a longer time to preserve the thermal stability of synthesized Ag NPs, and the use of toxic chemicals. Although these methods produce nanoparticles with high purity and well-defined morphology, it is critical to develop cost-effective, energy-efficient, and facile route, such as green synthesis; it suggests the desirable use of renewable resources by avoiding the use of additional solvents and toxic reagents in order to achieve the ultimate goal. However, each method has its pros and cons. The synthesized Ag NPs obtained using the green approach have larger biocompatibility and are less toxic towards the biotic systems. However, identifying the phytoconstituents that are responsible for nanoparticle synthesis is difficult and has been reported as a suitable candidate for biological application. The concentration of the effective bioreducing phytoconstituents plays a crucial role in deciding the morphology of the nanoparticle. Besides these reaction times, temperature, pH, and concentration of silver salt are some of the key factors that determine the morphology. Hence, careful optimization in the methodology is required as different morphologies have different properties and usage. It is due to which the development of methods to prepare nanoparticles effectively using various plant extracts is gaining rapid momentum in recent days. To make sense of what involves in the bioreduction of silver salt and to isolate the secondary metabolites from plants are yet challenging. This review focuses on the contribution of plant-mediated Ag NPs in different applications and their toxicity in the aquatic system.